2019
DOI: 10.7874/jao.2018.00381
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Feedback in the Simulated Patient Case-History Training among Audiology Students at the International Islamic University Malaysia

Abstract: Background and Objectives There is a scant evidence on the use of simulations in audiology (especially in Malaysia) for case-history taking, although this technique is widely used for training medical and nursing students. Feedback is one of the important components in simulations training; however, it is unknown if feedback by instructors could influence the simulated patient (SP) training outcome for case-history taking among audiology students. Aim of the present study is to determine whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, this is the first study where a role-play game has been applied to teaching in veterinary medicine. Role-play games are common practice in other disciplines such as physiotherapy [11,27], human medicine [9,32,33], and nursing [12,13], among others. Given the curricular similarities between these disciplines [34], acquiring this type of alternative teaching practices would be interesting for veterinary medicine students, from the point of view of active teaching and improving learning.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is the first study where a role-play game has been applied to teaching in veterinary medicine. Role-play games are common practice in other disciplines such as physiotherapy [11,27], human medicine [9,32,33], and nursing [12,13], among others. Given the curricular similarities between these disciplines [34], acquiring this type of alternative teaching practices would be interesting for veterinary medicine students, from the point of view of active teaching and improving learning.…”
Section: Discussionmentioning
confidence: 99%
“…As no assessment was conducted between simulation interviews with SPs and feedback sessions, it is unclear which contributed toward the improvement. In a study by Dzulkarnain et al, while conducting a simulated interview with SPs with hearing impairments, auditory history taking skills improved in the group that received feedback from the SPs than in the group that did not [11]. In addition, Brouwers et al…”
Section: Introductionmentioning
confidence: 99%
“…To unpack this complex interaction further, it is crucial to understand the impact from the sequence and timing of the interview and feedback on student performance and self-efficacy. Studies have shown how SP feedback following a simulated medical interview results in increased listening scores [ 11 ], neurological examination scores [ 12 ], and higher self-evaluation scores [ 13 ] compared with those who did not receive feedback. Such improvements are also not limited to feedback from SPs, as shown by Brouwers et al, who have demonstrated how feedback from doctors and peers is perceived as valuable by students [ 14 ].…”
Section: Introductionmentioning
confidence: 99%